Strategic Planning of Mahardhika Higher Education at the Mahardhika Institute of Technology and Health - Hadian, Mohamad Heri; Marlina, Reni; Suparman (Journal of Psychology and Sustainable Education, 2025)
This study explores in depth how strategic planning and standardization in higher education can be enhanced through the integration of Strengths, Weaknesses, Opportunities, and Threats (SWOT) analysis with the implementation of the Planning, Programming, Budgeting System (PPBS) model. The study was conducted at the Mahardika Institute of Technology and Health in Cirebon. It serves as a case study of a private higher education institution that strives to strengthen its academic and financial governance systems sustainably. This study employs a qualitative method with a case study design and a descriptive approach. In this study, data were collected through in-depth interviews, direct observation, and analysis of institutional documents. The findings reveal that integrating SWOT and PPBS enhances the effectiveness of strategic program development. Then, it improves efficiency in budget allocation and promotes institutional accountability to stakeholders. The study underlines that the success of implementing such strategies heavily depends on the readiness of human resources. Then, the availability of integrated information systems and an organizational culture that supports continuous evaluation and reflection. Based on these findings, it is recommended that higher education institutions adopt data-driven, integrated management models to achieve adaptive, efficient, and quality-oriented governance.